Top of the feud chain : an Alphas novel - Harrison, Lisi (Harrison, Lisi. Alphas., 2011)
"Alpha Academy: Where betas get booted. Eccentric billionaire Shira Brazille founded the super-exclusive Alpha Academy on exotic Alpha Island to nurture the next generation of exceptional dancers, writers, musicians, and inventors. It' s a dream come true for one hundred lucky girls, but those not measuring up can be sent home at any time, for any reason. The one left standing will win worldwide fame. Who will it be?"--Page 4 of cover.